Hyper up-algebras - Daniel A. Romano (Journal of Hyperstructures, 2019)
In this paper, the concept of hyper UP-algebras is introduced and some related properties are investigated. Also, theconcepts of hyper UP-ideals have been introduced and analyzed.In addition, the concept of homomorphisms between hyper UPalgebras is also considered.